2011
DOI: 10.1186/1471-2407-11-238
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 gene expression in colon cancer tissue related to regulating factors and promoter methylation status

Abstract: BackgroundIncreased cyclooxygenase activity promotes progression of colorectal cancer, but the mechanisms behind COX-2 induction remain elusive. This study was therefore aimed to define external cell signaling and transcription factors relating to high COX-2 expression in colon cancer tissue.MethodTumor and normal colon tissue were collected at primary curative operation in 48 unselected patients. COX-2 expression in tumor and normal colon tissue was quantified including microarray analyses on tumor mRNA accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The inhibition of COX-2 may suppress the growth of HCA-7 and Moser-S colon cancer cells (35). Increased COX-2 activity has a positive effect on the progression of colorectal cancer (36). The present study demonstrated that the expression levels of RhoA and the downstream factors, c-myc, c-fos, and COX-2 proteins, were decreased significantly in vivo due to ART1 gene silencing, and increased with ART1 overexpression in CT26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of COX-2 may suppress the growth of HCA-7 and Moser-S colon cancer cells (35). Increased COX-2 activity has a positive effect on the progression of colorectal cancer (36). The present study demonstrated that the expression levels of RhoA and the downstream factors, c-myc, c-fos, and COX-2 proteins, were decreased significantly in vivo due to ART1 gene silencing, and increased with ART1 overexpression in CT26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Asting et al . observed higher expression of prostaglandin synthetase in CRC cells [ 30 ]. The difference is the result of different populations being studied.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic knock-out or pharmacological inhibition of COX-2 has been shown to protect against experimentally-induced carcinogenesis [ 47 ]. Furthermore, more and more studies focus on the announcement of new transcriptional regulators of COX-2 [ 24 , 25 ]. Therefore, it is interesting and more significant to find out the unknown specific factors in regulating COX-2 expression in cancer cells and further explore how COX-2 is activated by these regulatory factors during tumorigenesis and development.…”
Section: Discussionmentioning
confidence: 99%
“…There are CAAT/enhancer binding protein (C/EBP) and cAMP response elements in the 5′-terminal nucleotide sequence. There are also some other protein binding sites in these gene sequences, such as the activator protein-2 (AP-2), the nuclear factor-kappa B (NF-κB) [ 24 , 25 ] and some transcriptional co-activators such as p300/CBP [ 26 , 27 ]. The expression of COX-2 is strictly and specifically regulated by these proteins.…”
Section: Introductionmentioning
confidence: 99%